Rare Earth Chemistry - Pöttgen, Rainer; Jüstel, Thomas; Strassert, Cristian A. (Walter de Gruyter GmbH, 2020)
This work introduces into the chemistry, materials science and technology of Rare Earth Elements. The chapters by experienced lecturers describe comprehensively the recent studies of their characteristics, properties and applications in functional materials. Due to the broad range of covered topics as hydrogen storage materials, LEDs or permanent magnets this work gives an up-to-date presentation of this fascinating research.
Keywords: Rare earths metals.; elektronické knihy; electronic books